Project Knowledge Retention in Social Messaging Application - Ismail, Shahrinaz (2018)
Project knowledge is as important as organisational knowledge since it is at the operational level of an organisation.The common ways of retaining knowledge from key employees are merely performed when the people intend to leave the organisation, whereas the retention of knowledge should be done on-goingly during the implementation of projects and tasks. It is also to mitigate knowledge loss during the process of project implementation. With the current technology of social messaging applications being taken for granted as communication tool alone, little did we realise the potential of the tool to be knowledge repository as well. Hence, this research analyses the commonly used social messaging application to understand the personal knowledge management processes within the conversation, in which the signs of knowledge retention happens.Qualitative data gathered from the conversation scripts is analysed to produce quantitative results.The outcome of this research is a proposed measurement technique for project knowledge retention in social messaging application, in which the mapped weight age of personal knowledge management processes is recommended to be used in project knowledge retention scoring model.